2023
DOI: 10.3390/cancers15072131
|View full text |Cite
|
Sign up to set email alerts
|

Optical Genome Mapping in Routine Cytogenetic Diagnosis of Acute Leukemia

Abstract: Cytogenetic aberrations are found in 65% of adults and 75% of children with acute leukemia. Specific aberrations are used as markers for the prognostic stratification of patients. The current standard cytogenetic procedure for acute leukemias is karyotyping in combination with FISH and RT-PCR. Optical genome mapping (OGM) is a new technology providing a precise identification of chromosomal abnormalities in a single approach. In our prospective study, the results obtained using OGM and standard techniques were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Around 20% of leukemic blasts are required for SNP‐array in a diagnostic setting for large CN alterations 34 , 35 . Our study and others 14 , 36 , 37 showed that OGM performance on samples with blast amounts of about 20%–30% could also detect alterations observed by conventional diagnostic methods. Hence, OGM could be an attractive option for routine diagnostic workup of hematological malignancies, as it has a fast turnaround time of ≈5 days from sample acquisition to data analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Around 20% of leukemic blasts are required for SNP‐array in a diagnostic setting for large CN alterations 34 , 35 . Our study and others 14 , 36 , 37 showed that OGM performance on samples with blast amounts of about 20%–30% could also detect alterations observed by conventional diagnostic methods. Hence, OGM could be an attractive option for routine diagnostic workup of hematological malignancies, as it has a fast turnaround time of ≈5 days from sample acquisition to data analysis.…”
Section: Discussionsupporting
confidence: 61%
“…Highly repetitive regions, such as centromeric regions, short arms of acrocentric chromosomes, pseudo-autosomal regions (PARs), and telomeric regions, are often poorly covered by OGM because of missing labels and unreliable reference map data. Consequently, OGM may fail to detect SVs involving these regions, a well-known limitation [ 14 - 17 ]. However, as these regions may contain clinically relevant SVs, efforts should be undertaken to identify recurrent SVs in these areas.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed OGM results of diagnostic samples from patients with hematologic malignancies and evaluated their concordance with the results of conventional methods in detecting SVs. Several recent studies have assessed the clinical usefulness of SV detection using OGM in patients with blood cancer [13][14][15][16][17][18][19][20][21]. These studies mainly used CBA, FISH, RT-PCR, CMA, or MLPA as conventional methods for comparison.…”
Section: Introductionmentioning
confidence: 99%
“…This is becoming increasingly important in newer technologies that depend on high molecular weight DNA for analysis, such as long-read sequencing and optical genome mapping [8,18]. Protocols for these applications can generate even longer DNA fragments ranging from 30 kb to 2000 kb [19][20][21]. High molecular weight DNA allows for more precise detection of large structural variants that are often associated with tumors that are genomically unstable [9,22].…”
Section: Discussionmentioning
confidence: 99%